ANALISIS LAYANAN PRIMA PADA RESTORAN CEPAT SAJI SUBWAY INDONESIA MALL KOTA KASABLANKA - Aaliyah Putri Syakira; Christian Wiradendi Wolor; Eka Dewi Utari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Excellent service is a key factor in building customer satisfaction and loyalty in the fast food restaurant industry. This study aims to analyze the implementation of excellent service at Subway Indonesia outlet in Kota Kasablanka Mall, focusing on service quality, work systems, and obstacles faced. The research method uses a qualitative approach with a case study design. Data were collected through observation, interviews with four employees (two supervisors and two sandwich artists), and documentation. The results of the study indicate that excellent service has been implemented quite well through speed, friendliness, and compliance with SOPs. The work system is supported by theoretical and practical training and customer satisfaction evaluation. The obstacles found include lack of staff during peak hours, customer diversity, and inconsistency of internal policies. Team coordination has been proven to be able to reduce obstacles, but increased training, number of staff, and policy standardization are recommended to optimize service.